Comparison of the productivity, cost and stem breakage of two- and three-machine harvest systems clearfelling a mature Pinus radiata stand. Issue 2 (2nd April 2020) - Strandgard, M.; Mitchell, R.
ABSTRACT: Damage to trees and logs during harvest and transport can result in major losses of wood volume and value. The study compared a harvester/forwarder (two-machine) harvest system, which typically is used in Australia, with a feller-buncher/processor/forwarder (three-machine) harvest system in terms of productivity, cost and felling stem breakage when clearfelling a 29-year-old Pinus radiata plantation in eastern Victoria, Australia. The study aimed to determine whether the three-machine harvest system reduced felling tree breakage while maintaining or improving on the productivity and delivered cost of the two-machine harvest system. The harvest systems were compared on adjacent sites ( 1 ha each) using an elemental time study. Machine productivity was derived from cycle times using StanForD stem files to obtain merchantable tree volumes and forwarder load weights from the forwarder's onboard scales. The three-machine harvest system was more productive and resulted in considerably less felling stem breakage than the two-machine harvest system (two broken stems compared with 21 broken stems). However, it was approximately 41% more expensive than the two-machine harvest system in terms of cost per m 3 of logs delivered to roadside. Because chiplogs were cut from broken stem sections where possible, and it was unlikely that sawlog volume was lost through stem breakage (based on the minimum sawlog specifications and the length and large-end diameter of the broken stem sections), any financial losses resulting from the additional breakage in the two-machine harvest system were insignificant compared with the extra cost per m 3 of logs delivered for the three-machine harvest system.